2017
DOI: 10.1039/c7ra05356h
|View full text |Cite
|
Sign up to set email alerts
|

Improved color stability of complementary WOLED with symmetrical doped phosphors in single host: experimental verification and mechanism analysis

Abstract: The complementary white device with symmetrically arranged dopants in a single host exhibits improved color stability with CIE coordinates' change less than (±0.020, ±0.010) at a wide driving voltages in the range 4 V to 9 V.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…So, the color stability is as important as other performance parameters such as brightness, device efficiency, and CRI. [27][28][29][30][31] Although many groups have reported the high device efficiencies for hybrid WOLEDs, the problems, including low CRI and poor color stability, still exist.…”
mentioning
confidence: 99%
“…So, the color stability is as important as other performance parameters such as brightness, device efficiency, and CRI. [27][28][29][30][31] Although many groups have reported the high device efficiencies for hybrid WOLEDs, the problems, including low CRI and poor color stability, still exist.…”
mentioning
confidence: 99%
“…two complementary colors) while retaining a high CRI is considered to be one of the most effective methods, since it would vastly simplify the device structure of the WOLED. 6,11,12,15 It is found that the acceptor (Bepp 2 ) of the above yellow exciplex is not only a widely used electron transporting material, but is also a highly efficient blue uorescent emitter with a high uorescent quantum yield of >0.80. 22 And the PL emission peak for Bepp 2 is located at about 450 nm, which is complementary to the yellow emission of m-MTDATA and Bepp 2 forming the exciplex.…”
Section: Resultsmentioning
confidence: 99%
“…White organic light-emitting diodes (WOLEDs) have been recognized as a promising alternative display and solid-state lighting technology due to the advantages of low-voltage operation, fast response, wide-viewing angle, easy fabrication of a potentially large area and mechanical exibility. [1][2][3][4][5][6][7] For lighting applications, the color rendering index (CRI) is an important indicator because the object under different light sources may look different due to the different colors of the reected light from the light sources. It is therefore crucial to develop ultra-high-CRI white-light illumination (CRI $ 90), especially for lighting applications in hospitals, art galleries, museums, and other special commercial places, etc.…”
Section: Introductionmentioning
confidence: 99%
“…High-efficiency WOLEDs based on UEMLs are typically prepared using multiple doped EMLs. However, the performance of doped EMLs is highly sensitive to doping concentrations and depends heavily on precise doping ratios during the co-evaporation process, leading to increased complexity in fabrications, especially in WOLEDs with high CRIs, where precise controls of guest concentrations in each EML are necessary to achieve a balanced white emission with high efficiency [101]. The use of undoped UEMLs show the potential to reduce production costs due to their simple fabrication process [102].…”
Section: Doping-free Woleds With Uemlsmentioning
confidence: 99%